A Review on Reliability Modeling of Manufacturing Systems Considering the Production Quality and Equipment Reliability - Li, Kewu; Yang, Jun; Huang, Shuo (Recent Patents on Engineering, 2021)
Background: Nowadays, the manufacturing industry is much more fiercely competitive and global than ever before. For sustainable increases in market share and profitability, manufacturers are aiming to improve the quality of products and maintain the reliability of manufacturing systems. Objective: Therefore, to simultaneously optimize the quality and reliability for manufacturing systems has become an important research topic in recent years. Methods: This study presents an overview of the methods for modeling manufacturing systems, especially considering the system reliability and the product quality. And then, we review the optimization methods for manufacturing system maintenance and production strategy. Conclusion: Finally, optimization methods and some challenges are summarized for future studies.
Keywords: maintenance strategy